2007
DOI: 10.1192/bjp.bp.106.024877
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol and post-traumatic stress disorder in adults

Abstract: Low cortisol levels in PTSD are only found under certain conditions. Future research should elucidate whether low cortisol is related to gender or abuse and depends on the measurement methods used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
434
5
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(464 citation statements)
references
References 47 publications
22
434
5
3
Order By: Relevance
“…In addition, a DEX challenge revealed that a single bout of massive footshock did not produce an alteration to the HPA axis's ability to provide reliable negative feedback. This falls in agreement with human literature that individuals with PTSD do not exhibit chronically elevated levels of cortisol (e.g., Meewisse et al 2007;Yehuda and Seckl 2011). Because we did not sample blood at shorter time points (30, 60, 90 min) following footshock it is unclear when exactly CORT is normalized within this study.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a DEX challenge revealed that a single bout of massive footshock did not produce an alteration to the HPA axis's ability to provide reliable negative feedback. This falls in agreement with human literature that individuals with PTSD do not exhibit chronically elevated levels of cortisol (e.g., Meewisse et al 2007;Yehuda and Seckl 2011). Because we did not sample blood at shorter time points (30, 60, 90 min) following footshock it is unclear when exactly CORT is normalized within this study.…”
Section: Discussionsupporting
confidence: 92%
“…45,46 Psychological comorbidities have been shown to affect cortisol secretion patterns. 47,48 We cannot address this issue in our study because we did not collect data on psychological comorbidities. Another possible limitation of this study is that salivary cortisol measures were taken on a single workday.…”
Section: Study Limitationsmentioning
confidence: 99%
“…A number of explanations for this heterogeneity of results are conceivable: given the high complexity of PTSD, potential explanations include betweenstudy differences in patient characteristics such as gender, disease comorbidity, medication or drug intake as well as severity, type and frequency of traumatic events (e.g. Rasmusson et al, 2003;Meewisse et al, 2007). In addition to these, it is however also likely that methodological factors associated with the assessment of cortisol might have contributed to the inconsistency of results (Meewisse et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rasmusson et al, 2003;Meewisse et al, 2007). In addition to these, it is however also likely that methodological factors associated with the assessment of cortisol might have contributed to the inconsistency of results (Meewisse et al, 2007). The HPA axis constitutes a highly dynamic system which is influenced by a range of situational factors (e.g.…”
Section: Introductionmentioning
confidence: 99%